Aerial Drones Reveal the Dynamic Structuring of Sea Turtle Breeding Aggregations and Minimum Survey Effort Required to Capture Climatic and Sex-Specific Effects - Dickson, Liam C. D.; Tugwell, Hannah; Katselidis, Kostas A.; Schofield, Gail (Frontiers in Marine Science, 2022)
Quantifying how animals use key habitats and resources for their survival allows managers to optimise conservation planning; however, obtaining representative sample sizes of wildlife distributions in both time and space is challenging, particularly in the marine environment. Here, we used unoccupied aircraft systems (UASs) to evaluate temporal and spatial variation in the distribution of loggerhead sea turtles (Caretta caretta) at two high-density breeding aggregations in the Mediterranean, and the effect of varying sample size and survey frequency. In May–June of 2017 to 2019, we conducted 69 surveys, assimilating 10,075 inwater turtle records at the two sites. Optimal survey frequency to capture the dynamics of aggregations over the breeding period was <2-week intervals and >500 turtles (from the combined surveys). This minimum threshold was attributed to the core-area use of female turtles shifting across surveys in relation to wind direction to access warmer nearshore waters and male presence. Males were more widely distributed within aggregations than females, particularly in May when mating encounters were high. Most males were recorded swimming and oriented parallel to shore, likely to enhance encounter rates with females. In contrast, most females were generally stationary (resting on the seabed or basking), likely to conserve energy for reproduction, with orientation appearing to shift in relation to male numbers at the breeding area. Thus, minimum survey frequency depends on what factors regulate movement and distribution, and will likely vary across sites globally. Our study demonstrates the versatility of UAS to capture the fine-scale dynamics of wildlife aggregations and associated factors, which is important for implementing effective conservation.